Mechanical Characterisation of Printed Nanosheet Network Thin Films - Sinnott, Aaron (Trinity College Dublin. School of Physics. Discipline of Physics, 2024)
The response of materials to applied stress and the resulting deformation is a fundamental cornerstone of condensed matter physics and materials research. From exciting new prospects such as the conductive nanosheet networks formed from printed two-dimensional material dispersions like graphene, to more longstanding puzzles such as the fundamental nature of plasticity in the entangled threads of polymer glasses, there exists a host of poorly understood mechanisms and interactions yet to be unravelled by the scientific community. On top of this, means for accurate and comprehensive mechanical exploration of thin film materials has only recently been made possible due to new nanomechanical advances, opening up further unexplored avenues of investigation. In this work, I perform explorations into the nanomechanical properties and processing of thin films of disordered matter ranging from complex printed networks of graphene and MoS2 nanosheets to glassy polymers. These materials, though differing in fundamental structure, can be examined using a common nanomechanical framework. Using carefully aligned flat punch indentation of stiffly supported thin films, I implemented the recently developed layer compression test which allows for in situ constitutive analysis of compressive stress vs strain behaviour providing close approximation to a uniform, confined uniaxial strain state to compressive strains well beyond the plastic yield point. A finite element exploration was performed to examine the degree of fidelity to uniaxial strain as a function of tip diameter to film thickness aspect ratio, 𝛼, and film to substrate modulus ratio, 𝑆. It was found that utilising a simple analytical substrate correction, variations to within 1% error are achievable with typical experimental parameters. The uniform compression imposed by the layer compression test was utilised experimentally to perform the first explorations of pressure dependent mechanics of thin film polystyrene and sprayed graphene nanosheet networks. This revealed a 45% stiffening in the regime of elastic compression up until the yield point for both materials, despite large fundamental morphological differences between them. Yielding of thin film PMMA was also observed in the layer compression test, in contrast to previous studies which found that PMMA would not yield in a compressive uniaxial strain geometry. This was attributed to an increase of shear compared to pure uniaxial strain, introduced by the layer compression test contact geometry. Micropatterned polystyrene thin films were also prepared via spherical tip compression to probe densification using β-NMR spectroscopy, which probes the sidegroup relaxation dynamics via the decay anisotropy of implanted 8Li. A clear reduction in relaxation rate was observed for micropatterned film in comparison to an unpatterned counterpart. The layer compression test was further utilised to explore the compressive mechanical nature of printed nanosheet network thin films of liquid phase exfoliated graphene and MoS2. A viscoelastic response was observed, owing to the combined sheet bending and slippage modes of deformation present. Important mechanical properties such as the effective elastic moduli and yield stress and strain were measured and quantified for networks with a range of parameters, with changes to these properties from densification also measured. The results were compared favourably to a folding sheet model adapted from crumpled sheet mechanics. Creep experiments were performed to quantify time dependent mechanics under applied strain, and the effect of chemical cross linking on the mechanical nature of MoS2 networks was also explored. Strain recovery and morphological changes with compression were analysed on the compressed network regions using focused ion beam cross sections and electron microscope tomography to gauge the compatibility of the networks with mechanical post processing for morphological improvements. Significant strain recovery was noted over long timescales, limiting the potential of compressive post processing. However, recovery was noted to drop significantly with introduction of shear deformation, and more extremely to near zero magnitude at a sharply defined stress point, dubbed the lock-in point. This lock-in phenomena was also associated with a distinct change in mechanical response of the networks, indicating a fundamental change in material behaviour at this point that is maintained in ambient conditions for graphene networks when pressure is removed. This lock-in point provides promising avenues for post processing and further exploration. In summary, this work provides the first nanomechanical exploration of sprayed nanosheet network thin films for applications in printed electronics and shines light on various processes of deformation as well as previously unknown pressure induced behavioural changes, with implications for the manufacture and operation of a range of printed electronic technologies.
APPROVED
Keywords: Nanoindentation; Nanomechanics; Graphene; Printed Electronics; Nanosheets; Functional Inks; Polymer; Thin Film; Densification